An Error Analysis of Students’ Writing Descriptive Text at Grade XI in SMK Taman Siswa Suka Damai Academic Year 2021/2022 - Weni Indah Sari; Lis Supiatman; Harry Sambayu (English Teaching and Linguistics Journal (ETLiJ), 2022)
This research was conducted to analyze the students’ error in writing descriptive text and what are the students’ dominant errors in writing descriptive text. The objective of this research was to analyze and describe the students’ error and to analyze and describe the dominant error made by the grade XI students of SMK Tamansiswa Sukadamai. This research used document analysis in collecting and analyzing the data. The subject of this research was the eleventh grade students at SMK Taman Siswa Suka Damai in 2021/2022 academic year which consisted of 25 students. Firstly, students were given essay test about descriptive text. Afterwards, the data were analyzed and classified the error by using the surface strategy taxonomy. The technique of collecting data was essay test. The researcher used the technique of analyzing the data from Dulay theory (1982) surface strategy taxonomy. The result of the research showed that there were error of omission is 35 (24%), error of addition is 11 (8%), error of misformation is 94 (64%), and error of misordering is 6 (4%). Based on the result of students’ test, the highest percentage of the test result in writing recount text is misformation with a percentage rate of 64%, it means misformation is the dominant error faced by students.